National survey of blindness and low vision in The Gambia: results. Issue 2 (February 1989) - Faal, H; Minassian, D; Sowa, S; Foster, A
Abstract : A population based survey of blindness and eye disease has been conducted throughout the whole country of The Gambia, and 8174 people were examined. The prevalence of blindness (best acuity less than 3/60) was 0.7% and low vision (6/24-3/60) 1.4%. The causes of blindness were cataract (55%), non-trachomatous corneal opacity/phthisis (20%), and trachoma (17%). An estimated 5500 people in The Gambia require cataract surgery, 4600 eyelid surgery for entropion, and 4600 people spectacles to correct a refractive error which causes a visual acuity of less than 6/18. More than half the current burden of blindness in The Gambia is potentially remediable through the provision of cataract surgery and aphakic spectacles.